2012
DOI: 10.1007/s00018-012-1145-8
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor of cytokine signaling 1 blocks mitosis in human melanoma cells

Abstract: Hypermethylation of SOCS genes is associated with many human cancers, suggesting a role as tumor suppressors. As adaptor molecules for ubiquitin ligases, SOCS proteins modulate turnover of numerous target proteins. Few SOCS targets identified so far have a direct role in cell cycle progression; the mechanism by which SOCS regulate the cell cycle thus remains largely unknown. Here we show that SOCS1 overexpression inhibits in vitro and in vivo expansion of human melanoma cells, and that SOCS1 associates specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 64 publications
2
12
0
Order By: Relevance
“…In our data, the overexpression of SOCS‐1 induced a decrease in the expression of anti‐apoptotic proteins, Mcl‐1 and Bcl‐xl, and significantly increased caspase‐3 activity in a dose‐dependent manner. In studies of cell cycle regulation, stable SOCS‐1‐transfected melanoma cells have been reported to lead to the G1/S transition defect, a secondary blockage in mitosis and accumulation of cells in the metaphase . Our study also shows that the overexpression of SOCS‐1 induced the G0/G1 arrest in G361 and SK‐MEL5 cells (Fig.…”
Section: Discussionsupporting
confidence: 69%
“…In our data, the overexpression of SOCS‐1 induced a decrease in the expression of anti‐apoptotic proteins, Mcl‐1 and Bcl‐xl, and significantly increased caspase‐3 activity in a dose‐dependent manner. In studies of cell cycle regulation, stable SOCS‐1‐transfected melanoma cells have been reported to lead to the G1/S transition defect, a secondary blockage in mitosis and accumulation of cells in the metaphase . Our study also shows that the overexpression of SOCS‐1 induced the G0/G1 arrest in G361 and SK‐MEL5 cells (Fig.…”
Section: Discussionsupporting
confidence: 69%
“…However, recent studies have demonstrated that SOCS1 could be directly implicated in tumor suppression by blocking mitosis in melanoma cell lines. In particular, SOCS1 was shown to reduce protein levels of G1 phase regulators of cell-cycle, such as cyclin D and cyclin E levels, and alters M phase protein levels through Cdh1 degradation [49]. Evidence of a direct role of SOCS3 in tumor progression in terms of disruption of cell cycle does not exist, likely due to the fact that SOCS3, differently from SOCS1, cannot localize in the cell nucleus, since it lacks of a nuclear translocation domain [50].…”
Section: Discussionmentioning
confidence: 99%
“…Adenovirus-mediated overexpression of SOCS1 can prevent HPV-related cells transformation by inducing degradation of the E7 oncoprotein 9 . SOCS1 overexpression inhibits in vitro and in vivo expansion of human melanoma cells, and SOCS1 associates specifically with Cdh1, triggering its degradation by the proteasome 103 . Enforced expression of SOCS1 leads to be resistant to transformation due to oncogenic induction 104 .…”
Section: Therapeutic Implicationsmentioning
confidence: 99%